Peran Layanan Konseling Dalam Menangani dan Mencegah Kasus Bullying di Sekolah - Ahmad Bahauddin; Hamidah Hamidah; Hizbul Hamzah (PGMI ISMAA, 2025)
Abstract: Bullying is a serious and persistent issue in educational environments, with significant impacts on students’ psychological, social, and academic well-being. To address this phenomenon, counseling services play a strategic role as both preventive and curative interventions aimed at reducing and managing the negative effects of bullying. This study employs a literature review method to explore the effectiveness of counseling services—individual counseling, group counseling, and crisis counseling—as psychological interventions that provide emotional support, strengthen student resilience, and restore victims' psychological stability. Individual counseling facilitates self-understanding and personal problem-solving, while crisis counseling offers immediate support for students experiencing emotional distress due to bullying. The findings indicate that counseling services are effective in creating safe spaces for students to express their feelings and receive guidance toward recovery. However, several challenges remain in implementation, including low awareness among students about the importance of counseling, an unbalanced counselor-to-student ratio, and limited facilities and support from schools and parents. Therefore, strategic efforts are required to enhance the quality of counseling services through counselor training, policy support, and the integration of technology to support modern counseling delivery. With a strengthened and holistic counseling system, schools can play a more optimal role in creating a safe, healthy, and bullying-free learning environment.